Flat-band ferromagnetism in twisted bilayer graphene - Pons, Rebecca; Mielke, Andreas; Stauber, Tobias (Physical review, 2020)
We discuss twisted bilayer graphene (TBG) based on a theorem of flat-band ferromagnetism put forward by Mielke and Tasaki. According to this theorem, ferromagnetism occurs if the single-particle density matrix of the flat-band states is irreducible and we argue that this result can be applied to the quasi-flat-bands of TBG that emerge around the charge-neutrality point for twist angles around the magic angle θ∼1.05∘. We show that the density matrix is irreducible in this case, thus predicting a ferromagnetic ground state for neutral TBG (n=0). We then show that the theorem can also be applied only to the flat conduction or valence bands, if the substrate induces a single-particle gap at charge neutrality. Also in this case, the corresponding density matrix turns out to be irreducible, leading to ferromagnetism at half filling (n=±2).
Gesehen am 02.02.2021